A concise review on surface and structural modification of porous zeolite scaffold for enhanced hydrogen storage - Bashir, Abubakar Abdulkadir; Rahida S.R., Mohd Zaki; A. T., Abd Wahab; Siti Nurqurratulainie, Miskan; Nguyen, Anh Tam; Vo, Dai Viet N.; Herma Dina, Setiabudi (Materials China, 2024)
Investigating zeolites as hydrogen storage scaffolds is imperative due to their porous nature and favorable physicochemical properties. Nevertheless, the storage capacity of the unmodified zeolites has been rather unsatisfactory (0.224%–1.082% (mass)) compared to its modified counterpart. Thus, the contemporary focus on enhancing hydrogen storage capacities has led to significant attention towards the utilization of modified zeolites, with studies exploring surface modifications through physical and chemical treatments, as well as the integration of various active metals. The enhanced hydrogen storage properties of zeolites are attributed to the presence of aluminosilicates from alkaline and alkaline-earth metals, resulting in increased storage capacity through interactions with the charge density of these aluminosilicates. Therefore, there is a great demand to critically review their role such as well-defined topology, pore structure, good thermal stability, and tunable hydrophilicity in enhanced hydrogen storage. This article aimed to critically review the recent research findings based on modified zeolite performance for enhanced hydrogen storage. Some of the factors affecting the hydrogen storage capacities of zeolites that can affect the rate of reaction and the stability of the adsorbent, like pressure, structure, and morphology were studied, and examined. Then, future perspectives, recommendations, and directions for modified zeolites were discussed.